ECOFUN Ladder Media in Elementary School Dance Arts Learning - Ezadya Anania Swasti Putri; Deasylina Da Ary (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Teachers’ limited ability to effectively integrate instructional media in classroom settings often results in student disengagement and reduced motivation to participate in learning activities. Such conditions create a less conducive environment and prompt the development of the ECOFUN Ladder as an innovative instructional medium for the Dance Arts curriculum in second-grade elementary education. Employing a Research and Development (R&D) methodology, the study adopts the ADDIE model. The research was conducted with a sample of 20 second-grade students. Data were collected through observations, tests, questionnaires, and interviews, and subsequently analyzed using both quantitative and qualitative approaches. ECOFUN Ladder is designed as a creative medium that integrates a traditional game containing basic dance movement materials, serving both a play and learning activity, while utilizing recycled paper as its primary material. This media consists of three main components: basic dance movements material, game cards, and visual illustrations. Findings from expert feasibility assessments conducted by media and subject matter specialists classified the ECOFUN Ladder as highly appropriate for instructional use. Effectiveness evaluations involving teachers and students similarly indicated a high level of feasibility. Moreover, the effectiveness test's empirical results revealed a notable improvement in students’ mean performance scores. So, it can be concluded that ECOFUN Ladder media have proven feasible and effective for use in the Dance Arts Subject for class II elementary school, especially in the basic dance movements material. These findings affirm that the ECOFUN Ladder is both pedagogically sound and effective for enhancing the teaching of Dance Arts in second-grade classrooms, particularly in facilitating the mastery of fundamental dance movements.